Price transmission and market power in modern agricultural value chains - Johan Swinnen; Anneleen Vandeplas (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2014)
"Modern" agricultural markets are characterized by, among other things, quality requirements and vertical coordination. The nature of the industrial organization of the value chain depends on a variety of factors, such as local institutions, economic growth, demand, institutional infrastructure etc. In this paper we present a conceptual framework to explicitly integrate key characteristics of these "modern" agricultural markets and derive implications for price transmission and market power in these markets and value chains.
Keywords: 330